Ghrelin octanoylation by ghrelin O-acyltransferase: Unique protein biochemistry underlying metabolic signaling. (9th January 2019) - Hougland, James L.
Abstract : Ghrelin is a small peptide hormone that requires a unique post-translational modification, serine octanoylation, to bind and activate the GHS-R1a receptor. Ghrelin signaling is implicated in a variety of neurological and physiological processes, but is most well known for its roles in controlling hunger and metabolic regulation. Ghrelin octanoylation is catalyzed by ghrelin O -acyltransferase (GOAT), a member of the membrane-bound O -acyltransferase (MBOAT) enzyme family. From the status of ghrelin as the only substrate for GOAT in the human genome to the source and requirement for the octanoyl acyl donor, the ghrelin–GOAT system is defined by multiple unique aspects within both protein biochemistry and endocrinology. In this review, we examine recent advances in our understanding of the interactions and mechanisms leading to ghrelin modification by GOAT, discuss the potential sources for the octanoyl acyl donor required for ghrelin's activation, and summarize the current landscape of molecules targeting ghrelin octanoylation through GOAT inhibition.